2023
DOI: 10.3390/ma16175873
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Adsorption Removal of Phosphate from Rural Domestic Sewage by Waste Eggshell-Modified Peanut Shell Biochar Adsorbent Materials

Cancan Xu,
Rui Liu,
Lvjun Chen
et al.

Abstract: In order to promote the improvement of the rural living environment, the treatment of rural domestic sewage has attracted much attention in China. Meanwhile, the rural regions’ sewage discharge standards are becoming increasingly stringent. However, the standard compliance rate of total phosphorus (TP) is very low, and TP has become the main limiting pollutant for the water pollutants discharge standards of rural domestic sewage treatment facilities. In this study, waste eggshell (E) was employed as a calcium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Xiao [27] pointed out that anions such as Cl -, HCO 3 − and HPO 4 2inhibited MNZ degradation. There are two reasons for this phenomenon : one is the consumption of free radicals ( • OH and SO4 • -) by these coexisting ions, and the other is that they increase the pH of the solution.Xu [28] prepared nano-zero-valent iron-loaded peanut shell biochar to degrade emerging pollutants PPCPs in water, and investigated the effect of inorganic anions on the degradation system. It was found that inorganic anions inhibited the degradation of tetracycline, and the inhibition intensity of inorganic anions on TC removal was HCO 3 ->Cl ->HPO 4 2->SO 4 2->NO 3 -.…”
Section: Coexisting Substratesmentioning
confidence: 99%
“…Xiao [27] pointed out that anions such as Cl -, HCO 3 − and HPO 4 2inhibited MNZ degradation. There are two reasons for this phenomenon : one is the consumption of free radicals ( • OH and SO4 • -) by these coexisting ions, and the other is that they increase the pH of the solution.Xu [28] prepared nano-zero-valent iron-loaded peanut shell biochar to degrade emerging pollutants PPCPs in water, and investigated the effect of inorganic anions on the degradation system. It was found that inorganic anions inhibited the degradation of tetracycline, and the inhibition intensity of inorganic anions on TC removal was HCO 3 ->Cl ->HPO 4 2->SO 4 2->NO 3 -.…”
Section: Coexisting Substratesmentioning
confidence: 99%
“…20,23,24 efficient, scalable, low cost, low maintenance, and provides the opportunity for nutrient recovery. 12,13 Wastewater nutrient and pollutant removal with adsorption technologies has been implemented at various treatment scales (nonsewered systems, 14,15 rural, 16 lab-scale, 17 household, 18 and full-scale wastewater treatment 19 ). Several classes of wastewater adsorbents have been described, including natural and synthetic zeolites and clays, polymeric ion exchangers, activated carbon and biochar, chitosan and cellulose, and metal oxide nanoparticles.…”
Section: Introduction To Adsorption For Resource Recovery From Wastew...mentioning
confidence: 99%
“…Ensuring the adoption of resource recovery requires the development of technologies to selectively separate nutrients from waste streams. Various techniques exist for nutrient removal such as biological methods, struvite precipitation, air stripping, membrane filtration, and adsorption. Of these techniques, adsorption is a viable option because it is simple, efficient, scalable, low cost, low maintenance, and provides the opportunity for nutrient recovery. , Wastewater nutrient and pollutant removal with adsorption technologies has been implemented at various treatment scales (nonsewered systems, , rural, lab-scale, household, and full-scale wastewater treatment). Several classes of wastewater adsorbents have been described, including natural and synthetic zeolites and clays, polymeric ion exchangers, activated carbon and biochar, chitosan and cellulose, and metal oxide nanoparticles. …”
Section: Introduction To Adsorption For Resource Recovery From Wastew...mentioning
confidence: 99%